2019
DOI: 10.1001/jamanetworkopen.2019.5600
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning–Assisted Diagnosis of Cerebral Aneurysms Using the HeadXNet Model

Abstract: Key Points Question How does augmentation with a deep learning segmentation model influence the performance of clinicians in identifying intracranial aneurysms from computed tomographic angiography examinations? Findings In this diagnostic study of intracranial aneurysms, a test set of 115 examinations was reviewed once with model augmentation and once without in a randomized order by 8 clinicians. The clinicians showed significant increases in sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 191 publications
(143 citation statements)
references
References 33 publications
2
126
1
Order By: Relevance
“…8,9 However, providing rapid and accurate diagnostic imaging is increasingly difficult to sustain for many medical systems and radiology providers as utilization has expanded; for example, CTPA usage alone in the emergency setting has increased 27-fold over the past 2 decades. 10,11 Applications of deep learning have already shown significant promise in medical imaging including chest and extremity Xrays, [12][13][14][15] head CT, 16 and musculoskeletal magnetic resonance imaging (MRI). 17 But despite the potential clinical and engineering advantages for utilization of deep learning automated PE classification on CTPA studies, significant development challenges remain when compared to other applications.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, providing rapid and accurate diagnostic imaging is increasingly difficult to sustain for many medical systems and radiology providers as utilization has expanded; for example, CTPA usage alone in the emergency setting has increased 27-fold over the past 2 decades. 10,11 Applications of deep learning have already shown significant promise in medical imaging including chest and extremity Xrays, [12][13][14][15] head CT, 16 and musculoskeletal magnetic resonance imaging (MRI). 17 But despite the potential clinical and engineering advantages for utilization of deep learning automated PE classification on CTPA studies, significant development challenges remain when compared to other applications.…”
Section: Introductionmentioning
confidence: 99%
“…CTA images have been studied by combining a neural network segmentation model (the HeadXNet model) to augment diagnostic performance in the detection of aneurysms. 26 In this study, the clinicians showed significant increases in sensitivity, accuracy, and interrater agreement when they were augmented with the model. However, the lack of a reference standard and external data verification, as well as the focus only on nonruptured aneurysms of .3 mm, limited the generalization and further application of the model.…”
Section: Brief Overview Of Aimentioning
confidence: 72%
“…Explorations on DL combined with MRA have reported decent results for IA detection 23,24 . While CTA based CAD system has been rarely reported, and only two recently published studies can be found, to the best of our knowledge 25,26 . Notably, these models were trained in small sample size, without the gold standard, and were not tested in different scenarios, thus they were not adequate to apply in real-world clinical settings, which may fall into the 'AI chasm' 27 .…”
mentioning
confidence: 94%